The Situation of the Representatives of Statehood Period Elite in Soviet Lithuania: the Case of Petras Klimas - Bukaitė, Vilma (Genocidas ir rezistencija, 2011)
After Lithuania was occupied by the USSR, and lost its statehood, the cultural, political, and scientific elite who did not emigrate, or who could not conform to the new system, suffered reprisals which complicated their lives within the Soviet reality. Examination of the role of the individual’s intellectual activities, his lifestyle, as well as the role of his friends and acquaintances in strengthening the individual’s personal dignity as well as his psychological and social security would help to provide a better understanding of the survival strategy of the former members of the elite of independent Lithuania in the authoritarian state. The study is exacerbated by problems of defining the topic and the search for sources and contributors. This paper involves the case study method. Due to the abundance of sources and his unique fate, the biography of Petras Klimas, a signatory of the Act of Independence of Lithuania of 1918, a diplomat, and a historian, was selected. The diplomat, who was in charge of the Lithuanian Embassy in France between 1925 and 1943, was arrested in Grasse by officers of the Gestapo. In 1944, he was brought to Lithuania and was imprisoned in prison camps in the USSR between 1945 and 1954. When he returned to Lithuania he was nearly 64. In spite of the mediation of influential French politicians, Klimas did not get permission to return to his family who had stayed in France. Klimas communicated with them through letter writing, which has became the main source of the present research. After significant effort, his daughter visited him in Lithuania four times. Klimas’ emotional condition after he returned to Lithuania from exile was very similar to that of other prisoners of Soviet prison camps – he often felt sadness, anxiety, and despair. The situation of the ailing man with virtually no financial support from the state was aggravated by understanding that he was unemployable, was constantly short of money, and was separated from his family. Research helped to maintain his spiritual balance. The moral support of his family was also very important. However, his different experience gained abroad prevented him from fully understanding the distinctive features of the Soviet system, the true nature of reprisals, and their impact on the individual. In addition, members of a family tend to remember those other members of the family who they are separated from, as they were when they last saw them. To restore the relationship between close members of a family, who have changed considerably over time, requires reciprocal efforts. The family communicating solely though letters had to avoid the rhetoric which could have led the Soviet security to discontinue the correspondence, so part of the dangerous information is thought to have been coded. Klimas could not escape searching for a compromise with the regime: when he faced difficulties, he often sought help from Justas Paleckis, the then Chairman of the Supreme Council of the LSSR. Hoping that his memoirs would be published, the historian tried to observe the conjuncture of Soviet historiography in the text. However, the Lithuanian statesman could not give a positive evaluation of the regime that had drastically encroached on the statehood he had built, restricted his freedom, carried out reprisals against him, and separated him from his family. He could only openly discuss political issues and remember the period of statehood with like-minded people. Moral attitude, internal discipline, economic support from his family and friends, a feeling of solidarity with people of the same fate, and the possibility of openly sharing recollections of the good times and criticising the regime were very important for the former representatives of the elite in order to survive the hard post-reprisal period with dignity.